2022
DOI: 10.3390/nano12183242
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulation of the Ion-Assisted Deposition of Silicon Dioxide Thin Films

Abstract: A systematic study of the most significant parameters of the ion-assisted deposited silicon dioxide films is carried out using the classical molecular dynamics method. The energy of the deposited silicon and oxygen atoms corresponds to the thermal evaporation of the target; the energy of the assisting oxygen ions is 100 eV. It is found that an increase in the flow of assisting ions to approximately 10% of the flow of deposited atoms leads to an increase in density and refractive index by 0.5 g/cm3 and 0.1, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…An increase in the energy of the incident atoms leads to a decrease in the surface roughness. The dependence of the R h on the density of the assisting ions flow f in the MD simulation of the silicon dioxide film deposition was studied in [110]. It was found that the increase of f from 4% of density of the deposited atoms flow to 10% results in the decrease of R h from 0.57 nm to 0.34 nm.…”
Section: Results Of the Simulation Of Thin Optical Films And Film-for...mentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the energy of the incident atoms leads to a decrease in the surface roughness. The dependence of the R h on the density of the assisting ions flow f in the MD simulation of the silicon dioxide film deposition was studied in [110]. It was found that the increase of f from 4% of density of the deposited atoms flow to 10% results in the decrease of R h from 0.57 nm to 0.34 nm.…”
Section: Results Of the Simulation Of Thin Optical Films And Film-for...mentioning
confidence: 99%
“…Accordingly, the simulation time increases by n 1/2 times. To reduce the increase in simulation time, for the case of high-energy deposition, the MD cycle can be divided into two stages [110]. The first stage describes the energy transfer of incident atoms to the substrate and films.…”
Section: Technical Aspects Of Simulation Proceduresmentioning
confidence: 99%
“…Ion beam-assisted deposition is a common technique for preparing thin films with low absorption and high quality [ 23 , 24 , 25 , 26 ]. Combined with thermal evaporation, it can improve the optical and mechanical properties of thin films and obtain dense, uniform, and stable films.…”
Section: Thin Film Preparation and Analysismentioning
confidence: 99%
“…However, the sputtering mechanism is well known for its high costs and lack of mass production capability [5]. Since many recent advancements have been made in IAD coaters, studies of mass production of coated mirrors in laser applications have been reported elsewhere [6]. The objective of this paper is to investigate the feasibility of using IAD in the mass production of chirped mirrors mounted on a large umbrella-shaped substrate holder as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%